Development of android apps for image processing - Chen, Qian (2016)
With rapid development of mobile technology and image processing, mobile application involving image processing has been largely emerged in many fields. Android, a mobile operating system based on Linux kernel, has the largest installed base of all general-purpose operating systems. Now there are over one billion active Android users and the marketing of Android applications is still increasing. This report analyzes and compares the conventional image segmentation methods which all suffer from inaccuracy problems. It also proposes an effective interactive image segmentation algorithm based on color space. It mainly executes in two steps, firstly user is required to enclose a small sample region in the predefined region of interest. Then the programme will identify all the similar-color objects present in the image and label the connected components. Based on the selected component, the programme will recognize and classify the image into a specific category and display the meaning. The algorithm is implemented in MATLAB first and transferred to the Android application. The proposed method has significantly improved the segmentation and recognition accuracy. Both of the experiments can achieve an excellent and improved result. This programme can be applied in both entertainment and education. It has the recreation significance for people to process their images or photos as well as the education significance for students to understand the meaning of an image or an object.